Eye movement as a biomarker of impaired organizational strategies during visual memory encoding in obsessive–compulsive disorder - Minah Kim (Nature Portfolio, 2021)
Abstract The symptoms of obsessive–compulsive disorder (OCD) are largely related to impaired executive functioning due to frontostriatal dysfunction. To better treat OCD, the development of biomarkers to bridge the gap between the symptomatic-cognitive phenotype and brain abnormalities is warranted. Therefore, we aimed to identify biomarkers of impaired organizational strategies during visual encoding processes in OCD patients by developing an eye tracking-based Rey–Osterrieth complex figure test (RCFT). In 104 OCD patients and 114 healthy controls (HCs), eye movements were recorded during memorization of the RCFT figure, and organizational scores were evaluated. Kullback–Leibler divergence (KLD) scores were calculated to evaluate the distance between a participant’s eye gaze distribution and a hypothetical uniform distribution within the RCFT figure. Narrower gaze distributions within the RCFT figure, which yielded higher KLD scores, indicated that the participant was more obsessed with detail and had less organizational strategy. The OCD patients showed lower organizational scores than the HCs. Although no group differences in KLD scores were noted, KLD scores were significantly associated with organization T scores in the OCD group. The current study findings suggest that eye tracking biomarkers of visual memory encoding provide a rapidly determined index of executive functioning, such as organizational strategies, in OCD patients.